Design of a 5 GHz Microstrip Bandpass Filter Using the Coupled Line Method for Synthetic Aperture Radar (SAR) - Syukri Fajrin; Asrizal; Mona Berlian Sari; Khairi Budayawan (Research on Instrumentation, 2024)
The remote sensing system, commonly referred to as radar, enables the monitoring of the Earth's surface by transmitting and receiving reflected microwave signals. With advancements in technology, remote sensing systems can now produce visual outputs in the form of 2D and even 3D images with high resolution. Synthetic Aperture Radar (SAR) has become one of the preferred methods for remote sensing. Using microwave signals, SAR radar is not exempt from disturbances such as out-of-band frequencies, interference, and other issues, which result in unclear radar images and noise. Therefore, a bandpass filter is required to filter signals in SAR radar systems. The proposed filter is designed using a microstrip layout. Microstrip filters offer advantages such as ease of design, the ability to operate at higher frequencies, low profile, and easy integration with other devices. The filter is designed using the couple line method, with a substrate having a dielectric constant of 2.17 and a thickness of 1.6 mm. The proposed design is tailored to the characteristics of SAR, targeting a filter frequency of 5 GHz with a narrow bandwidth of approximately 10 MHz. Simulation results indicate that the filter achieves a center frequency of 5.01 GHz, a bandwidth of 50 MHz, an insertion loss of -2.7 dB, and a return loss of -28 dB. Measurements of the fabricated filter show a center frequency of 5.03 GHz, a bandwidth of 18 MHz, an insertion loss of -2.8 dB, and a return loss of -15.11 dB. Based on these findings, the microstrip bandpass filter designed using the couple line method can be effectively used for SAR applications.